PENGARUH HARGA, PROMOSI, DAN VIRAL MARKETING TERHADAP KEPUTUSAN MEMBELI PADA TOKO ONLINE â€œNUNU COLLECTIONâ€ MELALUI FACEBOOK - -, Rika Wahyuni (EKONOMIA, 2019)
This research aims to investigate the influence of pricing, promotion, and viral marketing on purchasing decisions of the online shop Nunu Colletion through Facebook. Sample as many as 90 respondents obtained using engineering incidental sampling. Meanwhile, the collection of data is done with online questionnaires of the online shop Nunu Collection customers that have made a purchase online. Multiple linear regression analysis used in this study to analyze the data statistically by using SPSS v23 statistical program tools.Â  Results from this study were the effect of variable pricing, promotion, and viral marketing positive significant influence on purchase decisions through the online shop Nunu Collection via Facebook. Promotion was variable that has most contributed. Through this research, the expectation of using Facebook as a tool to promote the online shop Nunu Collection product could be improved, because of every promotion could be directly received and prompt responded by consumers.